Evolution of Phenotypic plasticity in ecologically diverging populations of Arctic charr (Salvelinus alpinus) - Kristján Þórhallsson 1995- (2022)
Since intraspecific phenotypic diversity is the raw material for adaptive divergence, understanding its origin is important for understanding evolution and conservation of biodiversity. Intraspecific diversity mainly arises from genetic diversity and environmental factors. Developmental plasticity, the capacity of a genotype to produce different phenotypes, may influence phenotypic divergence. This was addressed by studying Arctic charr (Salvelinus alpinus) morphs in Iceland, that have adapted to life on different food sources, most notably along an axis of benthic-pelagic habitats. The main research questions were, 1) how do craniofacial traits in morphs with different ecological specialization differ, and 2) how does plasticity evolve in these traits? To answer these questions, morphometric analyses were done on craniofacial traits in Arctic charr from different populations that were subjected to benthic or pelagic feeding treatment. Linear measurements were made on photos of 1816 charr from 5 populations (a putative ancestor, two from a lake with highly derived morphs and two from a lake with less divergence) and 3 hybrids. ANOVA, ANCOVA and regression were used to compare differences among means and assess allometric slopes by morphs and treatments. The results indicated that some traits diverged from the ancestor, but to a different level depending on morph and lake, developmental plasticity varied by trait, and the responses in some traits corresponded to known adaptations along the benthic-pelagic axis. To iterate, there was an association between plasticity and adaptive divergence for some traits. There was no indication of inheritance of plasticity in specific traits, even though the parental types were plastic. The results shed light on the origins of morphological diversity. Þar sem útlitsbreytileiki innan stofna er grundvöllur náttúrulegs vals og aðlögunar, er mikilvægt að skilja tilurð hans til að fá betri skilning á þróun og varðveislu líffræðilegs fjölbreytileika. Útiltsbreytileiki stafar ...